Colloidal Au sphere and nanoflower-based immunochromatographic strips for sensitive detection of zearalenone in cereals. Issue 39 (28th September 2022) - Qiao, Weili; He, Baoshan; Ren, Wenjie; Zhao, Renyong; Suo, Zhiguang; Yan, Haoyang; Xu, Yiwei; Wei, Min; Jin, Huali
Abstract : The AuNFs and AuSPs were successfully synthesized for labeling antibodies. The AuSP-ICS and AuNF-ICS were successfully fabricated for sensitive ZEN detection. The AuNF-ICS exhibited satisfactory sensitivity and specificity. Abstract : Zearalenone (ZEN), also known as an F-2 toxin, is a secondary metabolite in the toxic Fusarium species with estrogen properties. ZEN and its derivatives can cause developmental and reproductive disorders in humans and other mammals. In this study, colloidal Au spheres (AuSPs) and Au nanoflowers (AuNFs) were used as signal labels to detect ZEN in cereals, and the critical factors affecting the sensitivity of the immunochromatographic strip (ICS), namely the volume of antigen, antibody, and probe quantities were optimized and compared in detail. Since the large specific surface area of AuNFs reduces the steric hindrance of proteins, it is more conducive to improving the fixation rate of antibodies and proteins. Compared with the traditional colloidal AuSP immunochromatographic strip (AuSP-ICS), the volume of the antibody used in the AuNF immunochromatographic strip (AuNF-ICS) was 0.6 times that in the AuSPs-ICS. At the same antigen volume, a lower amount of probe can achieve the desired visual detection effect and higher sensitivity. For the AuNF-ICS, the limit of detection (LOD) was as low as 0.08 ng mL −1 . ZEN could be detected quickly and accurately from 0.08–10.2 ng mL −1 . And the AuNF-ICS had a high degree of specificity and sensitivity to ZEN. In summary, the AuNF-ICS serves as a valuable tool in large-scale on-site detection of ZEN.